Skala Kesantunan pada Tuturan Direktif dalam Anime ReLIFE karya Tomo Kosaka Episode 1-55 - Agustina, Putri Safitri; Irmayanti, Desy (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang; Vol 5 No 1 (2023)DO - 10.24843/JS.2023.v05.i01.p09, 2023)
Speech acts are utterances that are used to express something so that the listener knows what it Speech acts are utterances that are used to express something so that the hearer knows what it means. This study discusses directive utterances. Directive utterances are utterances that are spoken to the speaker with the intention that the speaker does something the speaker wants or intends to do. In speaking, the use of language must be considered so as not to hurt the feelings of others. Therefore, when communicating, we must use polite language. To find out politeness in language can be seen with the politeness scale theory. This study discusses the directive politeness scale in the anime ReLIFE episodes 1-5. The politeness scale theory used is based on Leech's theory. In this study using qualitative methods with a descriptive ap-proach because in this study the results of the analysis are described in words. Based on the results of the analysis, it can be concluded that the most commonly found politeness scale is the social distance scale in directive utterances. This is due to the level of closeness between the speaker and the hearer.